Measurement and evaluation in human performance - Morrow, James R. Jr. 1947-; Mood, Dale; Zhu, Weimo 1955-; Kang, Minsoo (Physical education teacher)
"This book addresses the fundamentals of collecting and analyzing data of human performance and applying the results to real-life situations. Focusing on the core concepts of reliability and validity of data, the text provides tools for evidence-based decision making that can be applied to physical therapy, allied health professions, kinesiology, sport and exercise science, physical education, health, and fitness"